Analysis of Morphologic and Functional Outcomes in Macular Edema due to Central Retinal Vein Occlusion Treated with Intravitreal Dexamethasone Implant - Alfredo Niro; Giancarlo Sborgia; Alessandra Sborgia; Luigi Sborgia; Claudio Furino; Nicola Recchimurzo; Giovanni Alessio (Journal of Ophthalmology)
Purpose. To analyze anatomic and functional retinal changes and their correlation after intravitreal dexamethasone implant (DEX implant) in patients with central retinal vein occlusion- (CRVO-) related macular edema (ME) using optical coherence tomography and microperimetry. Methods. Fifteen treatment-naïve patients with functional impairment due to CRVO-related ME were enrolled in this prospective interventional case series. Main outcomes were best-corrected visual acuity (BCVA), retinal sensitivity (RS), and central retinal thickness (CRT). Secondary outcomes were ellipsoid zone (EZ) status and fixation behaviour. All patients underwent DEX implant and were retreated according to predefined criteria. Data were prospectively recorded at baseline and at month 1, 3, 6, 9, and 12. Correlation between main outcomes was analyzed. Results. Fifteen eyes of 15 patients (9 men, 6 women; mean age 61.8 ± 10.9 years) were included. BCVA and CRT significantly improved at all follow-up visits, while RS significantly improved at 3, 6, 9, and 12 months. EZ status and fixation behaviour did not change significantly. Baseline CRT had a significant negative correlation with BCVA and RS at different follow-up visits (r=−0.52  to −0.63, p≤0.04; r=−0.52, p=0.04; resp.). At all time points, there was not a significant correlation between CRT and BCVA and RS, while RS and BCVA showed a significant correlation, increasing over time (r=−0.72  to −0.89; p<0.001). Conclusion. DEX implant led to a significant morphofunctional improvement. Baseline CRT is predictive of changes of functional outcomes whose correlation increases over time after treatment.